(untitled) (Economic and Political Thought, 2011)
The article presents: a concept of a social enterprise from the European and American perspective; interpretational misunderstandings connected with equating a social enterprise only with the social aims of its functioning; a lack of social enterprise criteria fulfillment by thousands of non-profit organizations, foundations and associations in the Polish social and economic reality; the position of a social enterprise in the humanizing theory of business. The article also attempts to position a social enterprise in the theory of confirmation and to find there a place for it from the point of view of the European interpretation as well as the American one. It starts a discussion about the research into social enterprises carried out by the authors.